The axis of complement C1 and nucleolus in antinuclear autoimmunity - Wu, Shan; Chen, Junjie; Teo, Boon Heng Dennis; Wee, Seng Yin Kelly; Wong, Ming Hui Millie; Cui, Jianzhou; Chen, Jinmiao; Leong, Khai Pang; Lu, Jinhua (Frontiers in Immunology, 2023)
Antinuclear autoantibodies (ANA) are heterogeneous self-reactive antibodies that target the chromatin network, the speckled, the nucleoli, and other nuclear regions. The immunological aberration for ANA production remains partially understood, but ANA are known to be pathogenic especially in systemic lupus erythematosus (SLE). Most SLE patients exhibit a highly polygenic disease involving multiple organs but, in rare complement C1q, C1r or C1s deficiencies, the disease can become largely monogenic. Increasing evidence point to intrinsic autoimmunogenicity of the nuclei. Necrotic cells release fragmented chromatins as nucleosomes and the alarmin HMGB1 is associated with the nucleosomes to activate TLRs and confer anti-chromatin autoimmunogenecity. In speckled regions, the major ANA targets Sm/RNP and SSA/Ro contain snRNAs that confer autoimmunogenecity to Sm/RNP and SSA/Ro antigens. Recently, 3 GAR/RGG-containing alarmins have been identified in the nucleolus that helps explain its high autoimmunogenicity. Interestingly, C1q binds to the nucleoli exposed by necrotic cells to cause protease C1r and C1s activation. C1s cleaves HMGB1 to inactive its alarmin activity. C1 proteases also degrade many nucleolar autoantigens including nucleolin, a major GAR/RGG-containing autoantigen and alarmin. It appears that the different nuclear regions are intrinsically autoimmunogenic by containing autoantigens and alarmins. However, the extracellular complement C1 complex function to dampen nuclear autoimmunogenecity by degrading these nuclear proteins.